Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga Terhadap Keputusan Pembelian Konsumen Coffee Shop “Gula Kopi” - Purnama, Oka (Universitas Ciputra Surabaya, 2023)
Food and beverage industry has high level business competition due to the large number of entrepreneurs. Food and beverage entrepreneurs must be able to provide the best for consumers in order to be outstanding in competition. Entrepreneurs must be able to understand the factors that influence consumers’ purchasing decision, such as product quality, service quality, price, and others. This research is done to find out the influence of product quality, service quality, and price on purchasing decision of